Prevalence of Varroa and Acarapis woodi mites and Nosema in honey bee colonies of Kermanshah Province, Iran - Rezaei, F; Karimi-Dehkordi, M (Journal of the Hellenic Veterinary Medical Society, 2025)
Varroa and Acarapis woodi mites and Nosema are the most important bee pathogens and cause a lot of damage to the apiculture industry. This study aimed to investigate the infection of Varroa and Acarapis woodi mites and Nosema among bee colonies in Kermanshah. For this purpose, 25 apiaries with at least 50 colonies were randomly selected, and eight colonies from each apiary were randomly selected for sampling (200 colonies in total). From each colony, 100 adult bees were collected from around and inside the hive and transferred to the laboratory. Also, the bottom debris of each colony was collected separately in unique bags. A 5 × 5 cm piece of wax containing larval cells was also cut from each colony. Varroa debris and neonatal cells were examined for Varroa infection in adult bee samples in the laboratory. The experiments were performed on adult bees to determine infection with Acarapis and Nosema. The results showed that 88% of studied apiaries and 32.5% of colonies were infected with Varroa. Also, 16% of apiaries and 7% of colonies showed Acarapis woodi infection, while 76% of apiaries and 34% of colonies were infected with Nosema. Most Varroa infections were found in adult bees. The results show that high infection with bee parasites, especially Varroa and Nosema, in the apiaries of Kermanshah, requires structural reform, management, and training of beekeepers to reduce these risks.